2004
DOI: 10.1026/0044-3409.212.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Die Zentrale Exekutive als präartikulatorische Kontrollinstanz

Abstract: Zusammenfassung. Der vorliegende Beitrag beschäftigt sich mit der Spezifikation einer präartikulatorischen Kontrollinstanz bei der Sprachproduktion durch exekutive Prozesse im Sinne des Arbeitsgedächtnis-Modells von Baddeley (1997) . Der Kontrollprozess wird in Sprachproduktionsmodellen zur Korrektur intern entstandener Sprechfehler noch vor der Artikulation postuliert. In einem ersten Experiment wird innerhalb des Paradigmas des lexical bias effects ( Dell & Reich, 1981 ) geprüft, ob die Belastung der Zen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The suppression of taboo words was inferred from an augmented galvanic skin response, indicating the activation and inhibition of the corresponding speech plan. Additional evidence supporting the notion of centrally controlled pre-articulatory editing is provided by Hamm et al [ 30 ]. Their experiment on eliciting spoonerisms demonstrated that a secondary cognitive task that strains the central control system amplifies the occurrence of spoonerisms.…”
Section: Introductionmentioning
confidence: 65%
“…The suppression of taboo words was inferred from an augmented galvanic skin response, indicating the activation and inhibition of the corresponding speech plan. Additional evidence supporting the notion of centrally controlled pre-articulatory editing is provided by Hamm et al [ 30 ]. Their experiment on eliciting spoonerisms demonstrated that a secondary cognitive task that strains the central control system amplifies the occurrence of spoonerisms.…”
Section: Introductionmentioning
confidence: 65%